Diagnosis and Treatment of an Ununited Anconeal Process in a California Sea Lion (Zalophus californianus) - Alexander Schlake; Laurens Van Mulders; Moniek Dekkers; Anastasia Selini; Jamie A. MacLaren; Griet Vercauteren; Koen Chiers; Francis Vercammen; Jonas Spruyt (Animals, 2025)
Orthopedic conditions, congenital or acquired, are frequent reasons for presentation of companion animals to veterinarians [...]